ANALISIS VALIDITAS MODUL BERBASIS QUANTUM LEARNING TEMA KAYANYA NEGERIKU UNTUK KELAS IV SD - Marfilinda, Riri; Widya, Widya; Latifah, Latifah (Unversitas Katolik Santo Thomas, 2021)
The development of a module based on Quantum Learning with the theme Kayanya Negeriku aims to see the product design of a module based on Quantum Learning on the theme of richness of my country in grade IV SD, and to see the results of validation for thematic modules based on Quantum Learning on the theme of richness of my country in grade IV SD. This research was conducted at SD 33 Kalumbuk, Padang City. This research and development process is carried out using the 4-D model), namely defining, designing, developing, and disseminating. Can be trusted as follows: 1) the defining stage is conducting curriculum analysis and analyzing the needs of students, 2) the design stage, carried out by designing the material preparation specifications, preparing tools and materials and module design, the resulting product form in the form of modules / teaching materials using the Quantum Learning model, 3 ) the development stage, is the module validation stage, and the module revision stage. and the dissemination stage was not carried out because considering the conditions of the COVID-19 pandemic so it was not possible to enter the field.The development was carried out by testing the validity of the module by 3 aspects, namely the material aspect 1 with a value of 3.7 which was very valid category, the design aspect with a value of 3.7 which was very valid category, and the language aspect with a value of 3.6 which was very valid category. Based on the results of the validation of an integrated thematic module based on Quantum Learning, the theme of richness for my country, grade IV SD got an average score of 3.7 in the Very Valid category. This gives an idea that the modules developed are valid and can be used in integrated thematic learning.